READINESS FOR CLIMATE CHANGE: AN ANALYSIS OF SMALL-SCALE FISHERMEN IN TASIKMALAYA, WEST JAVA - Dita Agustian; Samuel Agus Triyanto; Setio Galih Marlyono (Universitas Mataram, 2025)
Climate change is a significant challenge that impacts various sectors, including fisheries. This study aims to determine the level of preparedness of fishermen, especially for small-scale fishermen in Tasikmalaya District in facing various impacts caused by climate change. The research method used is a quantitative and qualitative survey involving in-depth interviews with 41 local fishermen, participatory observation, and secondary data analysis. The results of the study indicate that the level of preparedness of small-scale fishermen in PPI Pamayangsari Tasikmalaya District is in the ready category with an index value of 79.2%. The preparedness indicator with the highest index value is the disaster warning system at 95%, and the lowest is resource mobilization at 66%. It is hoped that there will be further analysis of the socio-economic impacts on fishing households, such as changes in livelihoods, migration, education, and changes in gender roles in response to climate change.